Perceptions of Spatiality: Supramodal Meanings and Metaphors in Therapeutic Environments - Liddicoat, Stephanie (UI Scholars Hub, 2018)
This paper explores the perceptions of the spatiality of individuals who self-harm, with the aim of understanding the design aspects which foster supportive therapeutic environments. Analysis of responses found that there were key similarities in areas of perception of architectural interior space, refuting the commonly held view that all architectural response is purely subjective, and that subjective experience cannot be shared. Three examples of perceptions of interior therapeutic environments are discussed to highlight how the perceptions of spatiality of individuals who self-harm consists of a particular cluster of spatial understandings, behaviours and focuses, manifesting as a strong emotional overtone overlaid onto built environments. This includes common kinds of triggers and emotional reactions provoked by aspects of the built environment. This paper discusses architectural aspects in relation to subjectivity in perception, constructs of interiority, and the role of supramodal engagement in influencing perceptual responses to interior space. By understanding how individuals who self-harm experience a space, a greater comprehension of the design of these environments delivering mental health services may be enabled. This paper tables a series of research-derived design suggestions to facilitate supportive therapeutic spaces. This paper also proposes a series of further research directions to explore the relationships between constructs of interiority, the physical interior space, and the therapeutic function for which they are designed.